Application of the Trend Moment Method in Product Sales Forecasting at TB. Mitra Baru - Tito, Prans; Azhar, Asbon Hendra (Jurnal ICT : Information and Communication Technologies, 2025)
Advances in information technology have made it easier for companies to manage sales data and conduct forecasting to support decision-making. TB. Mitra Baru, a trading company, often faces challenges in predicting future product sales, which impacts stock availability and business planning. This study aims to design and implement a website-based sales forecasting system using the Trend Moment method, a time series method that utilizes a trendline equation based on the average value over time and sales volume. Sales data is used as input to generate predictions for the next period in a systematic and structured manner. Test results indicate that the Trend Moment method is capable of providing sales estimates with a relatively low error rate, thus providing a basis for consideration in inventory management and sales strategies. With this website-based system, TB. Mitra Baru can easily access actual sales reports and forecast results at any time in real time, thus supporting operational effectiveness and more informed decision-making.